2021
DOI: 10.1002/adsc.202101285
|View full text |Cite
|
Sign up to set email alerts
|

Ni‐Catalyzed Direct Carboxylation of Aryl C−H Bonds in Benzamides with CO2

Abstract: The direct carboxylation of inert aryl C−H bond catalyzed by abundant and cheap nickel is still facing challenge. Herein, we report the Ni‐catalyzed direct carboxylation of aryl C−H bonds in benzamides under 1 atm of CO2 to afford various methyl carboxylates or phthalimides, dealing with different post‐processing. The reaction displays excellent functional group tolerance and affords moderate to high carboxylation yields under mild conditions. Detail mechanistic studies suggest that a Ni(0)−Ni(II)−Ni(I) cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Substrates bearing either an electron‐donating group ( 1 g – 1 h , 1 l – 1 m , 1 p – 1 q , and 1 s ) or an electron‐withdrawing group ( 1 i – 1 k , 1 n – 1 o , 1 r , and 1 t ) on the phenyl ring showed good reactivities and gave the carboxylation products in moderate to high yields. Remarkably, strong withdrawing groups CN ( 1 j ) and CF 3 ( 1 k , 1 o and 1 r ) are also suitable for this reaction, which are not captable in C−H bond carboxylation [21d] . It is worth noting that no carboxylation occurred at C−OMe [25] and C−CN [26] bonds in the substrates, which are also known to undergo the oxidative addition to a Ni(0) center.…”
Section: Methodsmentioning
confidence: 99%
“…Substrates bearing either an electron‐donating group ( 1 g – 1 h , 1 l – 1 m , 1 p – 1 q , and 1 s ) or an electron‐withdrawing group ( 1 i – 1 k , 1 n – 1 o , 1 r , and 1 t ) on the phenyl ring showed good reactivities and gave the carboxylation products in moderate to high yields. Remarkably, strong withdrawing groups CN ( 1 j ) and CF 3 ( 1 k , 1 o and 1 r ) are also suitable for this reaction, which are not captable in C−H bond carboxylation [21d] . It is worth noting that no carboxylation occurred at C−OMe [25] and C−CN [26] bonds in the substrates, which are also known to undergo the oxidative addition to a Ni(0) center.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, nickel has attracted great attention for the carboxylation with CO 2 . 187 Functionalization of the C(sp 2 )–H bond or alkenes with CO 2 in the presence of nickel catalysts is the most straightforward pathway owing to its good atom-economy (Fig. 6).…”
Section: Thermochemical Carboxylationsmentioning
confidence: 99%
“…213 Initially, the authors started the investigation by employing a series of ligands with a combination of NiBr 2 Áglyme, ligands (Scheme 28B), Zn, MgCl 2 , and DMF at 40 1C. Ligands based on 2,2 0 -bipyridines and 1,10-phenanthrolines (182)(183)(184)(185)(186)(187)(188)(189) having substituents adjacent to the nitrogen atom exhibited regioselectivity towards 191, while tridentate ligands (188 and 189) were more selective towards 192 (Scheme 28C). The reason was investigated by the mechanistic studies, which indicated the formation of Z 1 -Ni I intermediates with rigid bidentate ligands, and tridentate ligands facilitated the formation of Z 1 -Ni II intermediates.…”
Section: Nickel-catalyzed Carboxylationmentioning
confidence: 99%
“…At the same time, employing metallic simple substances or organometallic reagents as reductants restricts the substrate scope. As a result, achieving the rapid conversion of catalytic CO 2 to formate under benign conditions remains difficult. In the carboxylation and cycloaddition reaction of CO 2 with olefins, epoxides, and other substrates, researchers have tried to find milder reaction conditions at more ambient temperatures and lower CO 2 pressures. However, the temperature and CO 2 pressure cannot be easily controlled simultaneously.…”
Section: Introductionmentioning
confidence: 99%